Transmisi dan Transformasi Tradisi Tafsir Dari Mesir ke-Nusantara: Kajian Tafsīr Qur’ān Karīm - Rosihon Anwar; Asep Abdul Muhyi (Tashwirul Afkar, 2022)
Mahmud Yunus was the first ulama of Nusantara who expand to al-Azhar, Cairo, Egypt. He studied with several leading ulama to study knowledge of the Qur’an and tafsīr. When he returned to Indonesia, Mahmud Yunus brought with him the traditions of the Qur’anic interpretation that he had found at al-Azhar, Cairo, Egypt, then poured them into the Book of Tafsīr Qur'an Karīm. This research aims to find out the knowledge transmission that was formed between the interpreters of al-Azhar, Egypt and Mahmud Yunus, and the forms of interpretation traditions contained in Mahmud Yunus' Tafsīr Qur'ān Karīm. In order to uncover the ideological transformation of the Nusantara interpretation in this study, the hermeneutic method is used. The research results indicate that there are several tafsīr traditions contained in Tafsīr Qur'ān Karīm, including the knowledge tradition of interpretation, where Mahmud Yunus adopted Mustafa al-Maraghi's thoughts while studying at al-Azhar in Cairo, Egypt. Also the tradition of social interpretation where Mahmud Yunus adopted the thoughts of Rasyid Ridha and Abduh. These traditions continue to develop up today, not even a few interpreters interpret the Qur'an with a scientific and social approach, such as Tafsīr al-Azhar by Hamka, Tafsīr al-Bayan by Hasbi Ashidiqi, Tafsīr al-Furqan by A Hasan, and tafsīr.